The Challenges of PAI Teachers in Fostering Students' Religious Character in the Digital Era - Arina Rahma; Nur Saidah (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
The rapid development of information technology has transformed the lives of adolescents, particularly in terms of religious character development, leaving Islamic Religious Education (IRE) teachers to face challenges such as the negative influence of social media, a lack of parental supervision, and a crisis of role models in the home and school. This study aims to identify the strategic role of PAI teachers in shaping the religious character of adolescents through the integration of technology and parental collaboration, using a qualitative approach with an in-depth literature review of primary and secondary sources related to PAI, religious character, and the impact of digitalization. Key findings confirm that PAI teachers play a central role through the following strategies: (1) integrating technology to create contextual and engaging PAI materials; (2) providing personal role modeling and intensive interaction; and (3) collaborating closely with parents as the key to successfully instilling Islamic values, thereby enhancing adolescents’ character resilience against digital temptations.